İş Hukukunda Ev Hizmetleri - (:unkn) unknown (My University, 2020)
ş hukukumuzda “ev hizmetleri” İş Kanu-nu’nun kapsamı dışında bırakılmıştır. Ev hiz-metlerini konu alan ayrı bir iş kanunu ise bu-lunmamaktadır. Dolayısıyla, bu alanda çalışan işçiler, Borçlar Kanunu kapsamında yer almak-tadırlar. Ancak, hukukumuzda “ev hizmetleri” kavramı tanımlanmamıştır. Bu nedenle, hangi işlerin bu kapsamda yer alacağı tam olarak belli değildir. İş Kanunu’nun, ev hizmetlerini kapsam dışı bırakan düzenlemesinin hukuki niteliği de tartışmalıdır. Yine, ev hizmetlerinin niteliği ve işin yapıldığı yer, ev hizmetleri ko-nulu iş sözleşmelerini diğer iş sözleşmelerin-den ayırmaktadır. Borçlar Kanunu’nda yer alan bazı düzenlemelerin, ev hizmetleri yönünden ayrıca değerlendirilmesi gerekecektir. Aşağıda tüm bu hususlar dikkate alınarak konu incele-necektir

In labour law, domestic services are exclud-ed from the scope of the Labour Act. There is no separate labour act on domestic services. Therefore, workers working in this field are covered by the Code of Obligations. How-ever, the concept of domestic services has not been defined in our law. For this reason, it is not clear exactly which jobs will be in-cluded in this scope. The nature of the labour act provision that excludes home services is controversial. Again, the quality of domestic services and the place of work distinguishes the contracts on domestic services from oth-er contracts. Some regulations in the Code of Obligations also need to be evaluated in term of domestic services. The subject will be examined below by considering all these is-sues
Domestic Services in Labour Law